Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12041-012-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiparent intercross populations in analysis of quantitative traits

Abstract: Most traits of interest to medical, agricultural and animal scientists show continuous variation and complex mode of inheritance. DNA-based markers are being deployed to analyse such complex traits, that are known as quantitative trait loci (QTL). In conventional QTL analysis, F2, backcross populations, recombinant inbred lines, backcross inbred lines and double haploids from biparental crosses are commonly used. Introgression lines and near isogenic lines are also being used for QTL analysis. However, such po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 38 publications
0
45
1
Order By: Relevance
“…However, most QTL studies identify intervals encompassing hundreds to thousands of genes. QTL studies typically use two or at most several parental accessions (Rakshit et al, 2012) and, therefore, evaluate only a small fraction of the natural variation in a species. In contrast, GWAS generally combines phenotype and single-nucleotide polymorphism (SNP) data from 100 or more accessions to identify loci with allele frequency correlations to phenotypic variation (Atwell et al, 2010;Fournier-Level et al, 2011) or environment .…”
mentioning
confidence: 99%
“…However, most QTL studies identify intervals encompassing hundreds to thousands of genes. QTL studies typically use two or at most several parental accessions (Rakshit et al, 2012) and, therefore, evaluate only a small fraction of the natural variation in a species. In contrast, GWAS generally combines phenotype and single-nucleotide polymorphism (SNP) data from 100 or more accessions to identify loci with allele frequency correlations to phenotypic variation (Atwell et al, 2010;Fournier-Level et al, 2011) or environment .…”
mentioning
confidence: 99%
“…Simulation studies showed that this method can increase statistical power and reduce type I error compared with composite interval mapping (CIM) and multiparent whole-genome average interval mapping (MPWGAIM). We demonstrated the method using a public Arabidopsis thaliana MAGIC population and a mouse MAGIC population.KEYWORDS best linear unbiased prediction; empirical Bayes; mixed model; polygene; restricted maximum likelihood; multiparental populations; Multiparent Advanced Generation Inter-Cross (MAGIC); MPP T HERE is an urgent need to develop and study multiparent advanced generation intercross (MAGIC) populations (Rakshit et al 2012). Along with nested association mapping populations (Yu et al 2008), the MAGIC population is called a second-generation mapping resource (Rakshit et al 2012).…”
mentioning
confidence: 99%
“…T HERE is an urgent need to develop and study multiparent advanced generation intercross (MAGIC) populations (Rakshit et al 2012). Along with nested association mapping populations (Yu et al 2008), the MAGIC population is called a second-generation mapping resource (Rakshit et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations